POLITICAL PATRONAGE OF ISLAMIC COMMUNITY ORGANIZATION OF JOXZIN (Jogjakarta Islamic Never Die) WITH PARTAI PERSATUAN PEMBANGUNAN (PPP) ISLAMIC POLITIC IN THE GENERAL ELECTION OF 2019 IN THE SPECIAL REGION OF YOGYAKARTA-INDONESIA - Subandi, Yeyen; Rochmah, Tri Hastuti Nur; Purwaningsih, Titin; Nurmandi, Acmad (International Journal of Psychosocial Rehabilitation, 2020)
After the reformation era with the fall of the New Order (Soeharto) in 1998, the internal conflict of the United Development Party (PPP) in Indonesia did not end until its time before the general elections in 2019. The impact of the internal conflict occurred in some regions. One of which was in the Special Region of Yogyakarta. The impact that happened was the practice of political patronage between Islamic community organizations Joxzin (Jogjakarta Islamic Never Die) with the PPP Islamic political parties with the intention and purpose of winning legislative candidates nominated by PPP. The majority of literature sources or previous studies have revealed and explained in political patronage that the position of the patron is above the client in terms of ownership of economic, social, or power resources. However, what happens in research done using social network analysis methods and NodeXL and NVivo 12 Plus get results precisely the client (Joxzin) has the power and power above the patron (PPP). One example that occurred was when Joxzin appointed someone to be the chairman of the United Development Party Branch Development Board (DPC PPP). Political patronage conducted by Joxzin paid off by their two winning legislative candidates whose PPP supported as members of the Regional People’s Representative Council in the city of Yogyakarta (Yogyakarta DPRD) and also in DPRD of Yogyakarta. In the future, Joxzin will continue to do political patronage with PPP and also affiliate with the Islamic political party.